2020
DOI: 10.1016/j.msard.2020.102452
|View full text |Cite
|
Sign up to set email alerts
|

Mild or no COVID-19 symptoms in cladribine-treated multiple sclerosis: Two cases and implications for clinical practice

Abstract: Background The use of disease-modifying therapies (DMTs) in multiple sclerosis (MS) could affect COVID-19 outcomes by modulating the immune response, which, in turn, might favor viral replication and/or confer protection from COVID-19 induced inflammatory response Case report We report on two MS patients treated with cladribine, with heterogeneous demographics and clinical features, who developed mild or no symptoms from COVID-19 and produced anti-SARS-CoV-2 antibodies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 11 publications
4
34
0
5
Order By: Relevance
“…This is in line with previous observations by other authors ( Dersch et al., 2020 ; Jack et al., 2020 ; Celius, 2020 ; Preziosa et al., 2020 ; De Angelis et al., 2020 ). COVID-19 has been reported in 52 patients treated with cladribine; only in 23 of them, SARS-CoV-2 infection was confirmed by a laboratory test (i.e., nasopharyngeal swab and/or serological test) ( Dersch et al., 2020 ; Jack et al., 2020 ; Celius, 2020 ; Preziosa et al., 2020 ; De Angelis et al., 2020 ). In the remaining 39 patients, COVID-19 was suspected according to clinical symptoms and laboratory tests were not performed or tested negative ( Jack et al., 2020 ; Preziosa et al., 2020 ).…”
supporting
confidence: 94%
See 2 more Smart Citations
“…This is in line with previous observations by other authors ( Dersch et al., 2020 ; Jack et al., 2020 ; Celius, 2020 ; Preziosa et al., 2020 ; De Angelis et al., 2020 ). COVID-19 has been reported in 52 patients treated with cladribine; only in 23 of them, SARS-CoV-2 infection was confirmed by a laboratory test (i.e., nasopharyngeal swab and/or serological test) ( Dersch et al., 2020 ; Jack et al., 2020 ; Celius, 2020 ; Preziosa et al., 2020 ; De Angelis et al., 2020 ). In the remaining 39 patients, COVID-19 was suspected according to clinical symptoms and laboratory tests were not performed or tested negative ( Jack et al., 2020 ; Preziosa et al., 2020 ).…”
supporting
confidence: 94%
“…In the remaining 39 patients, COVID-19 was suspected according to clinical symptoms and laboratory tests were not performed or tested negative ( Jack et al., 2020 ; Preziosa et al., 2020 ). In all reports, cladribine-treated patients had favorable outcomes, even in the presence of severe lymphopenia ( Dersch et al., 2020 ; De Angelis et al., 2020 ), with no deaths nor need for mechanical ventilation. Serological data were available only for eight patients; and only one of them did not develop antibody response following infection ( Preziosa et al., 2020 ).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The course of COVID-19 infection is mild in most patients [ 16 , 17 ]. Despite the published case reports, both the risk of infection and the course of COVID-19 in patients with MS are still unclear [ 15 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. It is known that patients with MS are generally more susceptible to infections [ 11 , 37 ], especially those with a higher degree of disability or serious comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it seems that cladribine does not increase the severity of COVID‐19 and does not disturb anti‐SARS‐CoV‐2 antibody production. Therefore, it has been suggested that cladribine could be considered as a proper drug in terms of COVID‐19 vaccination 42 …”
Section: The Effect Of Dmts On Ms Patients With Covid‐19mentioning
confidence: 99%